Biological characteristics and clinical follow-up in natural cases of canine transmissible venereal tumour - Ramirez Ante, Juan Carlos (2021)
The aim of this study was to evaluate whether there is any relationship between cytological subtypes, histopathological phases, and the response to vincristine sulfate treatment in canines naturally affected by canine transmissible venereal tumour (CTVT). In total, 52 cases of CTVT were evaluated in different breeds, ages and sex without finding a significant relationship between the cytological classifications and histopathology determined prior to chemotherapy and the duration of the chemotherapy. The results of did not show differences in factors such as partial response to treatment, degree of malignancy, metastasis or resistance to vincristine in treated dogs, and the prognosis for tumour involution could not be defined from the cytology or histopathological classification.